Differential Proteomic Analysis of Rickettsia prowazekii Propagated in Diverse Host Backgrounds - Tucker, Aimee M. (American Society for Microbiology, 2011)

(untitled)
The obligate intracellular growth of Rickettsia prowazekii places severe restrictions on the analysis of rickettsial gene expression. With a small genome, predicted to code for 835 proteins, identifying which proteins are differentially expressed in rickettsiae that are isolated from different hosts or that vary in virulence is critical to an understanding of rickettsial pathogenicity. We employed a liquid chromatography (LC)-linear trap quadrupole (LTQ)-Orbitrap mass spectrometer for simultaneous acquisition of quantitative mass spectrometry (MS)-only data and tandem mass spectrometry (MS-MS) sequence data. With the use of a combination of commercially available algorithms and in-house software, quantitative MS-only data and comprehensive peptide coverage generated from MS-MS were integrated, resulting in the assignment of peptide identities with intensity values, allowing for the differential comparison of complex protein samples. With the use of these protocols, it was possible to directly compare protein abundance and analyze changes in the total proteome profile of R. prowazekii grown in different host backgrounds. Total protein extracted from rickettsiae grown in murine, tick, and insect cell lines or hen egg yolk sacs was analyzed. Here, we report the fold changes, including an upregulation of shock-related proteins, in rickettsiae cultivated in tissue culture compared to the level for rickettsiae harvested from hen yolk sacs. The ability to directly compare, in a complex sample, differential rickettsial protein expression provides a snapshot of host-specific proteomic profiles that will help to identify proteins important in intracellular growth and virulence.